2010
DOI: 10.1039/b925355f
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of 1,4-Li2-C6H4 and its reaction with [(Ph3P)AuCl]

Abstract: The difficulty in generating 1,4-Li2-C6H4 utilising the lithium halogen exchange reaction on 1,4-Br2-C6H4, 1,4-I2-C6H4 and 1-Br-4-I-C6H4 is revisited and only on treatment of 1,4-I2-C6H4 with 2 molar equivalents of n-BuLi can 1,4-Li2-C6H4 1 be isolated in excellent yield. Treatment of 1 with two equivalents of [ClAu(PPh3)] gives [1,4-(Ph3PAu)2-C6H4] 2a in excellent yield. Subsequent treatment of 2a with 2.5 molar equivalents of PPh2Me, PPhMe2 or PMe3 affords the PPh3 substituted compounds [1,4-(LAu)2-C6H4] (L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 104 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…This distance is identical with the traditional contact limit for significant aurophilic interactions [33]. However, recent experimental work has demonstrated that aurophilic interactions may be structurally relevant up to Au···Au distances of 4.0Å [34], which is in accord with earlier theoretical predictions [35]. The aurophilic aggregation usually observed in the solid state for linear dicoordinate gold(I) complexes can give rise to three principal structural motifs, viz.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…This distance is identical with the traditional contact limit for significant aurophilic interactions [33]. However, recent experimental work has demonstrated that aurophilic interactions may be structurally relevant up to Au···Au distances of 4.0Å [34], which is in accord with earlier theoretical predictions [35]. The aurophilic aggregation usually observed in the solid state for linear dicoordinate gold(I) complexes can give rise to three principal structural motifs, viz.…”
Section: Introductionsupporting
confidence: 73%
“…An almost identical value of 2.14Å was published in 2009 by Hu et al [73]. In 2010, Flower and coworkers proposed a value of 2.0Å [34]. The most recent values, published by Batsanov in 2011 [74] and by Alvarez in 2013 [70], differ considerably: 1.97Å vs. 2.32Å.…”
Section: Introductionmentioning
confidence: 71%
“…The Au atoms are separated by 6.076(1)Å which precludes any possible aurophilic interaction. 30 Examining the geometrical parameters of 6 reveals that while the Au2-C1 bond distance [1.975 5 33 There are no precedents in the literature for coordination of this type of ligand to two transition metal centres, with the closest analogy being a recently published mixed K-Mn species resulting from the reduction of a neutral Mn(II) NHC complex by KC 8 . 34 Establishing a new methodology for accessing dinuclear organogold species under mild reaction conditions, the synthesis of 6 demonstrates the dual transmetallating ability of 2 which reacts differently with each equivalent of [ClAu(PPh 3 )].…”
Section: Double Transmetallation Reaction To a Au(i) Complexmentioning
confidence: 99%
“…The Au1-C1 and Au1-P1 bond lengths of 2.0419(9) Å and 2.295(3) Å respectively are comparable to those previously reported for similar complexes. [58][59][60][61] Interestingly, as shown in figure 2, the amine moiety of 5 is rotated away from the Au(I) centre, presumably in order to minimise non-bonding interactions with the phosphane ligand, and therefore has no interaction with the metal atom (d(Au1…N1) = 4.662(7) Å, C1-C2-C7-N1 torsion angle of 152.7(8)°). This is in contrast to 4 (figure 2) which exists as a C,N-Au chelate (d(Au1-N1) = 2.09(4) Å, C1-C6-C7-N1 torsion angle of 29(3)°) with the nitrogen coordinated to the more Lewis-acidic Au(III) centre.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%